Peran Kompetensi Kewirausahaan pada Karakteristik Kewirausahaan Terhadap Kinerja Usaha UMKM (Studi Empiris: Pedagang UKM Desa Jatibaru) - Suroso Suroso; Enjang Suherman (Universitas Batanghari Jambi, 2023)
Social restrictions during the MSMEs pandemic are being tested in their business continuity. The performance of SMEs has decreased significantly. Several government efforts have been made. However, more is needed. Internal factors, such as entrepreneurial characteristics and competencies, need to be improved to improve MSME performance. This study aims to examine the role of entrepreneurial competence as a mediator in the influence of entrepreneurial characteristics on the business performance of MSME traders. The research design is descriptive verification regarding the mediating role of entrepreneurial competence on entrepreneurial characteristics in influencing the performance of MSME traders. The population of this study was 120 MSME traders, and 92 respondents were sampled with the 5% slovin formulation by taking a random sample. Data analysis used is descriptive statistics and Sem Smart PLS analysis. The results of this study describe that the entrepreneurial characteristics of MSME traders are pretty strong, and the entrepreneurial competence and performance of MSME traders are quite good. On the other hand, entrepreneurial characteristics significantly influence entrepreneurial competence. Entrepreneurial competence influences MSME performance, while entrepreneurial characteristics can significantly affect the performance of SMEs either directly or mediated by entrepreneurial competence.